Synthesis of calcium phosphate nanomaterial from quail eggshell for cadmium removal from wastewater and its genotoxic/cytotoxic properties - Demir, Cansu; Bakirdere, Bengisu Ece; Zaman, Buse Tugba; Oner, Miray; Bozyigit, Gamze Dalgic; Ergenler, Aysegul; Turan, Funda; Nejati, Omid; Ozturk, Ayca Bal; Cetin, Gulten; Bakirdere, Sezgin (SPRINGER, 2024)
In recent years, pollutants released into the environment from various sources threaten environmental health. Rapid industrialization and the constantly increasing needs of people facilitate the release of more hazardous wastes into the ecosystem. The presence of pollutants in water resources causes a wide range of adverse effects. In this study, calcium phosphate nanomaterial (Ca-3(PO4)(2) NM) was synthesized from biological waste eggshells for the cadmium removal in synthetic domestic wastewater, and a treatment method was developed using these NMs. The Ca-3(PO4)(2) NMs were produced by using a biowaste which provides the synthesis procedure greener approach. The biogenic NMs were used to remove toxic cadmium ions from wastewater samples. Cytotoxicity and genotoxicity studies of the synthesized NMs were also carried out, and their possible effects on the health of living organisms and the ecology were examined. In the developed method, the parameters affecting the removal of cadmium from wastewater samples were optimized and the removal efficiency was calculated by determining cadmium in a flame atomic absorption spectrophotometer system (FAAS). Synthetic domestic wastewater samples were utilized for evaluating the applicability of the developed treatment strategy. In addition, the adsorption capacity of the material for Cd2+ ion was calculated and the values obtained were modeled by using Langmuir adsorption isotherm (LAI). The calculated LAI parameters were within the appropriate limits, which proved that the developed NM can be used as an effective material for cadmium removal. Moreover, a new, rapid, and feasible synthesis strategy for the synthesis of Ca-3(PO4)(2) NM was presented in the literature.
Keywords: Cadmium; Ca-3(PO4)(2) nanomaterial; Water treatment; Isotherm; Genotoxicity; Cytotoxicity; ACTIVATED CARBON; NANOPARTICLES; ADSORPTION; CHEMISTRY; METHODOLOGY; CD(II); IONS; Environmental Sciences & Ecology